27.4 Karjalan kieli Šuomešša: ELDIA-projektin tulokšie - Sarhimaa, Anneli
Abridged Karelian (Viena) translation of the report on the case study on the Karelian language in Finland, conducted within the EU-FP7 research project ELDIA